MAKTABGACHA YOSHDAGI BOLALARNI RITORIKA BILAN TANISHTIRISHNING AHAMIYATI - Shamuratova, X. (SCIENCE and SOCIETY, 2024)
The article analyzes the opinions of foreign scientists on introducing rhetoric to preschool children.